Benefit of unified halal certification in nigeria halal industry - Fatimah Ademola; Betania Kartika; Anis Najiha (Yayasan Azhar Amanaa Yogyakarta, 2024)
The first step in harmonizing, standardizing, and regulating halal practices in the nation is unification and standardization. But the halal market in Nigeria is still developing. The growing need for halal products draws businesses with or without an Islamic relationship to halal certification. In Nigeria's case, the certification is granted by both conventional and religious certifying agencies. Having an excessive number of halal certification suppliers without oversight of their operations can make it difficult to determine which firm to trust. This research aims to investigate the feasibility of establishing a uniform and consistent halal certification in Nigeria, in light of the existing misunderstanding. This essay examines the significance of having uniform frameworks for halal certification. The study uses a qualitative methodology, gathering data through library research and interviews. To address the study topic, a thematic analysis of the data is conducted. Increased consumer trust, easier market access for companies, and better regulatory control are all advantages of unification. This research supports a streamlined approach to Halal certification that fosters transparency, credibility, and market integrity globally through cooperation among certifying bodies, regulatory authorities, and industry stakeholders. This article suggests that, while achieving halal certification, unity is feasible.